2019
DOI: 10.1002/rth2.12193
|View full text |Cite
|
Sign up to set email alerts
|

Platelet function testing at low platelet counts: When can you trust your analysis?

Abstract: Background Although flow cytometry is often brought forward as a preferable method in the setting of thrombocytopenia, the relative effects of low sample counts on results from flow cytometry‐based platelet function testing ( FC ‐ PFT ) in comparison with light transmission aggregometry ( LTA ) and multiple electrode aggregometry ( MEA ) has not been reported. Objectives … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 23 publications
(42 reference statements)
0
19
0
Order By: Relevance
“…Furthermore, promising results are accomplished with platelet aggregation studies under flow conditions [28]. Advantages of these new methods are the use of whole blood and low sample preparation, but they also require trained technicians and specialized equipment [29][30][31][32][33][34]. Likewise, standardization of the traditional LTA method is still essential here.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, promising results are accomplished with platelet aggregation studies under flow conditions [28]. Advantages of these new methods are the use of whole blood and low sample preparation, but they also require trained technicians and specialized equipment [29][30][31][32][33][34]. Likewise, standardization of the traditional LTA method is still essential here.…”
Section: Discussionmentioning
confidence: 99%
“…Flow cytometry-based single cell analysis provides platelet assays, which are largely independent of platelet count and thereby feasible in blood from patients even with severe thrombocytopenia [ 95 , 96 ]. However, a recent study indicated that a platelet count of ≤10 × 10 9 /mL might influence in vitro platelet activation assays due to the platelet count-related decreased release of ADP, which serves as important amplifier of platelet activation [ 97 ]. Figure 2 gives an overview of important platelet phenotype and activation markers, which are determined by flow cytometry for the diagnostic purposes of platelet function defects potentially associated with thrombocytopenia.…”
Section: Specialized Platelet Function Testsmentioning
confidence: 99%
“…In recent years, several flow cytometry approaches have been successfully used to assess platelet function in patients with severe chronic immune thrombocytopenia, showing that impaired platelet function is associated with bleeding, independent of platelet count [ 76 , 77 , 78 ]. However, it should also be noted that simply decreasing the platelet count induces an impaired platelet function phenotype as measured by flow cytometry, due to the loss of paracrine amplification of platelet responses by ADP release [ 79 ]. This indicates that flow cytometric assessment of platelet function is affected by platelet count, admittedly to a lesser extent than other traditional platelet function assays, and highlights the importance of deriving platelet-count-adjusted reference ranges.…”
Section: Platelet Function Testing In Thrombocytopeniamentioning
confidence: 99%